Upaya Peningkatan Kompetensi Manajerial Kepala Madrasah dalam Perencanaan Rencana Kerja Madrasah Ibtidaiyyah di Kabupaten Purbalingga Tahun 2022 (Studi Kasus MIN 1 Purbalingga dan MI Maarif Purbalingga) - Nur Hidayah; Teti Ratnawulan; Siti Honiah; Ayi Najmul Hidayat; Titi Suwarni; Nahdiyah Hidayah (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2023)
This article presents the results of the author's inspirational research which provides an overview of the management of educational institutions within the Ministry of Religion of Purbalingga Regency. The aim of the study was to find out the efforts to increase the Managerial Competence of the Head of Madrasah Ibtidaiyyah in Purbalingga in Madrasah Work Planning. The approach in this study uses a qualitative approach through case studies. Data collection was carried out through the stages of both open and closed interviews, observation and documentation studies. The research results show that various efforts have been made by school heads at MIN 3 Purbalingga and MIS Maarif Purbalingga in improving their managerial competence in the planning aspect. This can be seen from the various steps taken to increase competency through improving educational qualifications by continuing to Masters and Doctoral degrees, education and training, MoUs with various tertiary institutions in increasing the managerial competence of Madrasah Principals, sharing good practices, and through comparative studies. As a result, the increase in these activities helped the Madrasah Principal plan a programmed Madrasah work plan starting from the preparation stage, identifying and reflecting on the results of the Madrasah Quality Report Card to the formulation of a Madrasah work program plan that involved all Madrasah residents. The recommendation from the results of this research is that it is necessary to increase the managerial competence of Madrasah Heads in Scheduled and Programmed Planning in order to improve the Quality of Ibtidaiyyah Madrasahs under the Ministry of Religion.